Vernalization Duration Requirement in Soft Winter Wheat is Associated with Variation at the VRN‐B1 Locus. Issue 5 (1st September 2014) - Guedira, Mohammed; Maloney, Peter; Xiong, Mai; Petersen, Stine; Murphy, J. Paul; Marshall, David; Johnson, Jerry; Harrison, Steve; Brown‐Guedira, Gina
ABSTRACT: Genetic variation in the factors controlling flowering in wheat ( Triticum aestivum L.) allow it to be grown in a wide range of environments. The aim of this study was to identify genetic determinants of flowering time in winter wheat cultivars adapted to regions of the United States differing in latitude and the duration of cold temperatures during winter. Quantitative trait locus (QTL) analysis was performed in a recombinant inbred line (RIL) population from the cross between cultivars NC‐Neuse and AGS 2000 that are adapted to the Mid‐Atlantic and Southeastern regions, respectively. We identified a QTL for heading date (HD) in the greenhouse after 4 wk of vernalization, designated Qvdr.nc‐5BL, which also had a large effect on winter dormancy release and HD when the population was evaluated in the field at locations in North Carolina, Georgia, and Louisiana during 2012 and North Carolina during 2013. However, Qvdr.nc‐5BL did not have a significant effect on HD in greenhouse grown plants vernalized for 8 wk or in plants grown in the field at Raleigh, NC during 2011. In those environments where Qvdr.nc‐5BL was not significant, a region on chromosome 2B, probably associated with the Ppd‐B1 locus, was determined to have a HD effect. Interrogation of the population with gene‐based markers for Vrn‐B1 and Ppd‐B1 suggests that these loci are major determinants of HD in winter wheat and are important for adaptation to diverse growing environments.